Impact of government-funded insulin pump programs on insulin pump use in Canada: a cross-sectional study using the National Diabetes Repository - Gillian L Booth; Alanna Weisman; Bruce A Perkins; Cimon Song (BMJ Open Diabetes Research & Care)
Introduction Insulin pump access in type 1 diabetes may be inequitable. We studied the association between government funding programs for insulin pumps and rates of insulin pump use and disparities between pump users and non-users.Research design and methods Adults with type 1 diabetes were identified in the National Diabetes Repository, a primary care electronic medical record database of individuals with diabetes from five Canadian provinces. Proportions of individuals using insulin pumps were compared between provinces with and without pump funding programs. Multivariable logistic regression models were used to estimate the odds of insulin pump use adjusting for confounders. Univariate logistic regression models were used to estimate the odds of insulin pump use according to each predictor, according to pump funding program status.Results Of 1559 adults with type 1 diabetes, proportions using insulin pumps were 47.8% (95% CI 45.1% to 50.5%) and 37.7% (95% CI 31.5% to 44.1%) in provinces with and without pump funding programs (p=0.0038). Adjusting for age, sex, HbA1c, income quintile, and rural/urban location, the OR for insulin pump use was 1.45 (1.08–1.94) for provinces with pump funding programs compared with provinces without. Higher income was associated with a greater odds of insulin pump use in provinces with pump funding programs, and rural/urban location was not associated with insulin pump use.Conclusions Insulin pump use is more common in regions with government funding programs. Further research is required to best understand and comprehensively address persistent income disparities between pump users and non-users despite the availability of reimbursement programs.